(untitled) (World Bulletin of Public Health, 2023)
Preterm labour (PL) is one of the most significant problems in maternal and child health, which currently does not tend to decrease. The risk of death in premature babies is 25–35 times higher than in full-term babies. And stillbirth with PL is recorded 8–13 times more often than with timely births. The severity of complications associated with prematurity is inversely proportional to gestational age. In general, PL is responsible for up to 70% of perinatal mortality. PL were designated at the last FIGO Congress (2018) as a problem that has not been solved and cannot be solved by modern methods. The lack of scientific foundations not only for the etiology, but also for the pathogenesis of PL does not allow one to achieve practical results either in the prevention or in the treatment of this complication of pregnancy